The Legal Case Method applied to the film "Judgment at Nuremberg" - Manzanero, Delia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The aim of this paper is to reflect and comment on certain scenes from Stanley Kramer’s film Judgment at Nuremberg based in the Case Method methodology used in university lessons to teach Law and Ethics. The judgement which this film addresses is extraordinary, being one in which judges themselves were judged by other judges; as such, it presents a perfect example through which to think about the social responsibility of the legal profession with respect to the application of Law and what relationship this has to broader moral and ethical considerations of the value of human rights.